HOLOGRAPHIC GRATING RECORDING IN “LYOTROPIC LIQUID CRYSTAL – VIOLOGEN” SYSTEM - Bordyuh, Hanna; Polishchuk, Arkadiy (Proceedings of National Aviation University (archive), 2014)
This work presents the results of nonlinear optical experiment run on the samples of lyotropic liquid crystal (LLC) with viologen admixtures. During the experiment we obtained dynamic grating recording on bilayered LLC-viologen samples and determined main characteristics of recoded gratings. It was found out that the recording takes place in a thin near-cathode coloured viologen layer. The analysis of kinetics of thermal gratings erasing showed that contribution of a thermal nonlinearity into general diffraction efficiency is negligible small. The last fact is connected with a separation of LLC-viologen samples under the action of an electric field and heat sink into the liquid crystal layer